Pemilihan Strategi Peningkatan Penjualan Produk Makanan Menggunakan Metode SWOT dan Quantitative Strategic Planning Matrix Pada UKM EL-Gans - Tanisri, Roberta Heni Anggit; Eka, Irfan; Apriyani, Apriyani; Nadia, Ainun (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2024)
El-Gans is one of small and medium business that in the process sells martabak. The decline in sales over the past six months has had an impact on the decline in the value of profits for business owners. This research is intended to provide an analysis of alternative sales strategies to increase sales from sweet martabak and at the same time to develop business in the food sector. The determination of strategy selection for El-Gans is carried out using the SWOT method approach and the Quantitative Strategic Planning Matrik (QSPM) method. The results of the SWOT matrix analysis found that the position of El-Gans is currently in quadrant two which is a business diversification position. The results of the calculation of alternative strategies using the QSPM method determined that El-Gans will implement the fifth alternative strategy, namely utilizing online sales applications more massively so that the El-gans brand name can be known by the wider public and be able to increase sales of its food products.